High levels of WNT-5A in human glioma correlate with increased presence of tumor-associated microglia/monocytes - Dijksterhuis, Jacomijn P; Arthofer, Elisa; Marinescu, Voichita D; Nelander, Sven; Uhlén, Mathias; Pontén, Frederik; Mulder, Jan; Schulte, Gunnar (Experimental cell research, 2015)
Malignant gliomas are among the most severe types of cancer, and the most common primary brain tumors. Treatment options are limited and the prognosis is poor. WNT-5A, a member of the WNT family of lipoglycoproteins, plays a role in oncogenesis and tumor progression in various cancers, whereas the role of WNT-5A in glioma remains obscure. Based on the role of WNT-5A as an oncogene, its potential to regulate microglia cells and the glioma-promoting capacities of microglia cells, we hypothesize that WNT-5A has a role in regulation of immune functions in glioma. We investigated WNT-5A expression by in silico analysis of the cancer genome atlas (TCGA) transcript profiling of human glioblastoma samples and immunohistochemistry experiments of human glioma tissue microarrays (TMA). Our results reveal higher WNT-5A protein levels and mRNA expression in a subgroup of gliomas (WNT-5A(high)) compared to non-malignant control brain tissue. Furthermore, we show a significant correlation between WNT-5A in the tumor and presence of major histocompatibility complex Class II-positive microglia/monocytes. Our data pinpoint a positive correlation between WNT-5A and a proinflammatory signature in glioma. We identify increased presence of microglia/monocytes as an important aspect in the inflammatory transformation suggesting a novel role for WNT-5A in human glioma.
Keywords: gliom; Male; Tissue Array Analysis; výpočetní biologie; monocyty; Proto-Oncogene Proteins; mužské pohlaví; čipová analýza tkání; proteiny Wnt; Wnt Proteins; Glioma; mikroglie; lidé; ženské pohlaví; Humans; Microglia; Monocytes; Female; Computational Biology; protoonkogenní proteiny